Environmental training is beneficial to clinical symptoms and cortical presynaptic defects in mice suffering from experimental autoimmune encephalomyelitis. (February 2019) - Bonfiglio, T.; Olivero, G.; Vergassola, M.; Di Cesare Mannelli, L.; Pacini, A.; Iannuzzi, F.; Summa, M.; Bertorelli, R.; Feligioni, M.; Ghelardini, C.; Pittaluga, A.
Abstract: The effect of "prophylactic" environmental stimulation on clinical symptoms and presynaptic defects in mice suffering from the experimental autoimmune encephalomyelitis (EAE) at the acute stage of disease (21 ± 1 days post immunization, d.p.i.) was investigated. In EAE mice raised in an enriched environment (EE), the clinical score was reduced when compared to EAE mice raised in standard environment (SE).Concomitantly, gain of weight and increased spontaneous motor activity and curiosity were observed, suggesting increased well-being in mice. Impaired glutamate exocytosis and cyclic adenosine monophosphate (cAMP) production in cortical terminals of SE-EAE mice were evident at 21 ± 1 d.p.i.. Differently, the 12 mM KCl-evoked glutamate exocytosis from cortical synaptosomes of EE-EAE mice was comparable to that observed in SE and EE-control mice, but significantly higher than that in SE-EAE mice. Similarly, the 12 mM KCl-evoked cAMP production in EE-EAE mice cortical synaptosomes recovered to the level observed in SE and EE-control mice. MUNC-18 and SNAP25 contents, but not Syntaxin-1a and Synaptotagmin 1 levels, were increased in cortical synaptosomes from EE-EAE mice when compared to SE-EAE mice. Circulating IL-1β was increased in the spinal cord, but not in the cortex, of SE-EAE mice, and it did not recover in EE-EAE mice. Inflammatory infiltrates were reduced in the cortex but not in the spinal cord of EE-EAE mice. Demyelination was observed in the spinal cord; EE significantly diminished it. We conclude that "prophylactic" EE is beneficial to synaptic derangements and preserves glutamate transmission in the cortex of EAE mice. This article is part of the Special Issue entitled "Neurobiology of Environmental Enrichment". Graphical abstract: Highlights: Enriched environment (EE) ameliorates clinical score and behaviours in EAE mice. Inflammatory infiltrates and spinal demyelination are reduced in EE-EAE mice. EE preserves glutamate exocytosis efficiency from cortical terminals. cAMP production from cortical synaptosomes is unaltered in trained EAE mice. EE increases the expression of MUNC-18 and SNAP-25 in the cortex.